Pediatric Normative Database of Retinal, Macular and Choroidal Values obtained with Spectral-Domain Optical Coherence Tomography - Queirós, Tatiana (2019)
Purpose: To establish normative values in a Portuguese pediatric population for retinal nerve fiber layer (RNFL), macular, macular ganglion cell-inner plexiform layer (GCIPL) and subfoveal choroidal (SFC) thicknesses  Methods: This cross-sectional study enrolled children, 4 to 17 years old, attending the Ophthalmology Department of Hospital de Braga. All subjects underwent comprehensive ophthalmologic examination and were scanned with Cirrus Spectral-Domain Optical Coherence Tomography (SD-OCT).  Results: A total of 348 children (9.85±3.49 years) were included. Average RNFL thickness was 97.45±9.78µm and the distribution of RNFL thickness was in agreement with the ISNT rule. Average RNFL thickness showed a positive significant relationship with optic disc (OD) area (p=0.007). A significant positive relationship was also found for OD area (p=0.001 and p=0.04, respectively) and spherical equivalent (SE) (p=0.008 and p=0.004, respectively), in the inferior and nasal quadrants. Average macular thickness was 282.22±11.91µm. Central subfield was the thinnest region, followed by the external ring, while the internal ring was the thickest (p<0.001). Age, SE and gender were the strongest predictors of macular thickness. A negative association was found between the superior external macular thickness and age (p=0.009). A lower thickness in the outer macular region was associated with higher myopic refractive error (p<0.05). Boys had on average a thicker macula (p<0.05). Average GCIPL thickness was 84.97±4.78 µm and average SFC thickness was 374.76±42.51 µm.  Conclusion: This study established a SD-OCT normative database for healthy Portuguese children aged 4 to 17 years old, which could improve diagnosis and management of pediatric ophthalmic disorders in children.